2018
DOI: 10.1038/s41598-018-26761-2
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin attenuates Wnt signaling via upregulation of FZD6 to suppress prostate cancer stemness revealed by comparative proteomics

Abstract: The mechanisms underlying luteolin-induced inhibition of prostate cancer (PCa) stemness have remained elusive. Here, we report that luteolin suppresses PCa stemness through Wnt signaling by upregulation of FZD6 (frizzled class receptor 6). Luteolin inhibits PCa cell proliferation, migration, self-renewal as well as the expression of prostate cancer stem cell markers in vitro. Through iTRAQ-based quantitative proteomics study, we identified 208 differentially expressed proteins in luteolin-treated PC-3 cells. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…Luteolin inhibited the migration of PC-3 cells in transwell and wound healing assays. Moreover, it decreased spheroid formation and self-renewal (or stemness) of these cells by up-regulating frizzled class receptor 6, a negative regulator of the Wnt pathway, that plays an important role in tumorigenesis (133) . Another study using U-87 MG and U-251 MG glioblastoma cells demonstrated that luteolin inhibited epidermal growth factor receptor (EGFR) and its downstream Akt and MAPK signalling pathways.…”
Section: Luteolinmentioning
confidence: 99%
“…Luteolin inhibited the migration of PC-3 cells in transwell and wound healing assays. Moreover, it decreased spheroid formation and self-renewal (or stemness) of these cells by up-regulating frizzled class receptor 6, a negative regulator of the Wnt pathway, that plays an important role in tumorigenesis (133) . Another study using U-87 MG and U-251 MG glioblastoma cells demonstrated that luteolin inhibited epidermal growth factor receptor (EGFR) and its downstream Akt and MAPK signalling pathways.…”
Section: Luteolinmentioning
confidence: 99%
“…prostate and oral cancer (Tu et al, 2016;Han et al, 2018b) Naringenin anti-proliferation CCND1, EREG, ESR2, MAPK1/14 cervical, colon, colorectal cancer, and hepatocarcinoma (Totta et al, 2004;Song et al, 2015;Zhang et al, 2016) Targets Cancer types Ref inhibiting metastasis AKT1, CDH1, MAPK1/4, MMP2/9, NCL, NFKB, PKCZ, PKCE, RAC1, RHO, RHOA, SCN9A, SNAIL1/2, TGFB1, TWIST1, VIM breast, lung, and bladder cancer (Liao et al, 2014;Zhang et al, 2016;Chang et al, 2017;Aktas and Akgun, 2018;Han et al, 2018c;Zhao et al, 2019b) promoting apoptosis AKT1, MAP3K5, ATF3, BAX, BCL2, BIRC5, CASP3/9, JNK, MAPK1/3/14, TP53, RPS6KB1, ROS1, RPS6…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the spheres were used. iTRAQ analysis was performed as described previously [ 28 , 29 ] with minor modified. Briefly, SOX4-overexpressing HCT-116 and control cells were cultured in ultra-low attachment plate for sphere formation.…”
Section: Methodsmentioning
confidence: 99%